Efficient oxidation of ethyl benzene using in situ generated molybdenum acetylide oxo-peroxo complex as recyclable catalyst - Khomane, Sonali B.; Doke, Dhananjay S.; Dongare, M. K.; Halligudi, S. B.; Umbarkar, S. B. (Applied Catalysis A-General, 2017)
Selective oxidation of various alkanes/alkyl aromatics to corresponding carbonyl compounds has been carried out with very high conversion (similar to 98%) and selectivity (up to 100%) for carbonyl compounds using cyclopentadienyl molybdenum acetylide complex, CpMo(CO)(3)(C CPh) (1) as catalyst and tert-butyl hydrogen peroxide (TBHP) as an oxidant and turnover number (TON) of 88 was obtained with turnover frequency (TOF) of 2.45 h(-1). Mo acetylide oxo-peroxo species is formed in situ by reaction of 1 with TBHP during the course of reaction as catalytically active species. Interestingly even though the catalytically active species is homogeneous in nature it could be recycled very easily by recovering the catalytically active species as solid after addition of diethyl ether, and separating the products into organic phase. In the case of ethyl benzene oxidation, even after three recycles no appreciable loss in ethyl benzene conversion and acetophenone selectivity was observed. This complex showed high catalytic activity for the oxo functionalization of other alkyl aromatics and alkanes such as substituted ethyl benzenes, toluene as well as cyclohexane. TBHP was found to be more efficient oxidant than hydrogen peroxide for this oxidation. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Alkyl aromatics; Carbonyl compounds; Homogeneous catalysis; Molybdenum acetylide complex; Oxo-peroxo species

Cyclohexylation of resorcinol with cyclohexanol catalyzed by tungstophosphoric acid supported zirconia catalysts - Balasubramanian, V. V.; Devassay, B. M.; Halligudi, S. B.; Deepika, R.; Umbarakar, S. B.; Vinu, A. (Journal of Nanoscience and Nanotechnology, 2018)
We demonstrate a highly active and reusable heterogeneous catalyst system, tungstophosphoric acid (TPA) supported on zirconia (ZrO2), for the cyclohexylation of resorcinol by cyclohexanol to produce value added chemicals such as 2-cyclohexyl resorcinol, 4-cyclohexyl resorcinol and 3-Hydroxy cyclohexyl phenyl ether under liquid phase reaction condition. TPA/ZrO2 catalysts prepared with different TPA loadings (5-30 wt.%) by wet impregnation method and calcined in the temperature range of 650-850 degrees C were characterized by Nitrogen sorption analysis, XRD, FTIR, DTG and DTA, and P-31 MAS NMR spectroscopy. Among the catalysts studied, 15 wt.% TPA/ZrO2 catalyst calcined at 750 degrees C gave the highest conversion of resorcinol (51.2%) with the selectivities for 3-Hydroxy cyclohexyl phenyl ether (53.9%) and 2-cyclohexyl resorcinol and 4-cyclohexyl resorcinol together (46.1%) under optimum reaction conditions. However, the selectivity of the products were controlled by varying the reaction conditions. At higher conversion of resorcinol (78.9%), only C-alkylated products were formed at 200 degrees C with 15 wt.% TPA/ZrO2 catalyst calcined at 750 degrees C. The combination of TPA and ZrO2 coupled with calcination temperature offered an excellent platform for the conversion of resorcinol into O- or C-alkylated products.
Keywords: 15% TPA/ZrO2; Cyclohexanol; Cyclohexylation; Keggin TPA; Resorcinol

Efficacy of octahedral molecular sieves for green and sustainable catalytic reactions - Lucas, Nishita; Gurrala, Lakshmiprasad; Halligudi, S. B. (Molecular Catalysis, 2020)
Sustainability and Green Chemistry has emerged as catchphrase in modern era and researchers worldwide have embraced it as new paradigm of development. In this context identifying potential materials able to curb multiple grave issues thus contributing towards sustainability is vital. Catalytic materials are quite potent for addressing current social, economic and environmental problems like harnessing alternative energy source, pollution prevention/remediation and manufacturing of commodity chemicals. Thus, the present review accentuates the efficacy of porous octahedral molecular sieves (OMS) as catalyst for such environmentally important reactions. It discusses about structural importance of OMS and their applications for green and sustainable catalytic reactions. Finally, the limitations are highlighted and future perspectives are presented which will ameliorate its catalytic utilization in energy and environmental domains.
Keywords: catalytic transformations; Lignocellulosic biomass; octahedral molecular sieves; platform chemicals; renewable feedstock